Slipping through the net: the paradox of nursing's electronic theses and dissertations. - Macduff, C.; Goodfellow, L.; Nolfi, D.; Copeland, S.; Leslie, Gavin; Blackwood, Diana (Wiley-Blackwell, 2016)
AIM: The study's main aim was to gain in-depth understanding of how nurse scholars engage with electronic theses and dissertations. Through elicitation of opinions about challenges and opportunities, and perceptions of future development, the study also aimed to influence the design of a new international web-based forum for learning and sharing information on this topic. BACKGROUND: Electronic theses and dissertations provide an opportunity to radically change the way in which graduate student research is presented, disseminated and used internationally. However, as revealed by a multi-national survey in 2011, many nurse scholars in vanguard universities have little awareness of how to find and exploit this ever-expanding global knowledge resource that is increasingly available free in full text format. Within this context more detailed understandings of nurse scholars' thinking and actions are required. METHODS: A qualitative approach using a semi-structured interview guide was utilized to elicit perceptions from 14 nurse scholars. RESULTS: Thematic analysis of the interviewees' responses identified six major themes: initial exposure and effect; searching; accessing; handling; using; and evaluation. Insights were gained about the value of these resources and behaviours in using them as exemplars for structure, format and methodology.Conclusion and implications for nursing and nursing policy: Despite the small study size, the findings added valuable new insights to the overview gained from the 2011 survey. These have been used to inform development of a new global initiative: the International Network for Electronic Theses and Dissertations in Nursing. Featuring an educational website (www.inetdin.net), this initiative aims to support and challenge nursing's policy makers, practitioners and especially educators to utilize this neglected but exponentially increasing wellspring of international nursing knowledge.